Keynes's approach to money: an assessment after 70 years - L. Randall Wray (Levy Economics Institute of Bard College, 2006)
This paper first examines two approaches to money adopted by Keynes in the General Theory (GT). The first is the more familiar supply and demand equilibrium approach of Chapter 13 incorporated within conventional macroeconomics in both the ISLM version as well as Friedman's monetarism. Indeed, even Post Keynesians utilizing Keynes's finance motive or the horizontal money supply curve adopt similar methodology. The second approach of the GT is presented in Chapter 17, where Keynes drops money supply and demand in favor of a liquidity preference approach to asset prices. The Chapter 17 approach offers a much more satifactory treatment of the fundamental role played by money to constrain effective demand in the capitalist economy. In the next section, I return to Keynes's earlier work, namely the Treatise on Money (TOM), as well as the early drafts of the GT, to obtain a better understanding of Keynes's views on the nature of money.
Keywords: 330; Geldtheorie; Keynesianismus